If women rose rooted : the journey to authenticity and belonging - Blackie, Sharon (September Publishing, 2016)
Aged 30 Sharon Blackie found herself weeping in the car park of the multinational corporation where she worked, wondering if this was what a nervous breakdown felt like. With a PhD in Psychology she ought to have known. Somewhere along the line she realised she had lost herself. And so began a long winding journey back to authenticity, rootedness in place, and belonging. In this extraordinary book of myth memoir and modern day mentors Blackie faces the wasteland of Western culture, the repression of women, and the devastation of our planet. She boldly names the challenge to reimagine women's place in the world and to rise up firmly rooted in our own native landscapes and the powerful stories and wisdom which spring from them. If Women Rose Rooted offers a haunting heroine's journey for every woman who finds power inspiration and solace in the natural world.